Interfaces do político: o discurso de Alberto Pasqualini em perspectiva (1936-1955) - Almeida, Diego Orgel Dal Bosco (2015)
This thesis as main aim the study of the Alberto Pasqualini s political discourse. Considering the chronological boundary as being the period from 1936 to 1955, one looks for to consider the figure s inicial political trajectory in the hosts of the Liberator Party (PL) of the state of Rio Grande do Sul up to the moment of national projection of his political figure as one of the main and most influential leaderships in PTB (Brazilian Labor Party). The accurate comprehension of Alberto Pasqualini s inicial politics allows a scope resize of the analisis of the elements that pointed his public life.